Universal endometrial cancer tumor typing: How much has immunohistochemistry, microsatellite instability, and MLH1 methylation improved the diagnosis of Lynch syndrome across the population? - Kahn, Ryan M.; Gordhandas, Sushmita; Maddy, Brandon Paul; Baltich Nelson, Becky; Askin, Gulce; Christos, Paul J.; Caputo, Thomas A.; Chapman‐Davis, Eloise; Holcomb, Kevin; Frey, Melissa K. (Cancer, 2019)
Background Universal tumor testing for defective DNA mismatch repair (MMR) is recommended for all women diagnosed with endometrial cancer to identify those with underlying Lynch syndrome. However, the effectiveness of these screening methods in identifying individuals with Lynch syndrome across the population has not been well studied. The aim of this study was to evaluate outcomes of MMR immunohistochemistry (IHC), mutL homolog 1 (MLH1) methylation, and microsatellite instability (MSI) analysis among patients with endometrial cancer. Methods A complete systematic search of online databases (PubMed, EMBASE, MEDLINE, and the Cochrane Library) for 1990‐2018 was performed. A DerSimonian‐Laird random effects model meta‐analysis was used to estimate the weighted prevalence of Lynch syndrome diagnoses. Results The comprehensive search produced 4400 publications. Twenty‐nine peer‐reviewed studies met the inclusion criteria. Patients with endometrial cancer (n = 6649) were identified, and 206 (3%) were confirmed to have Lynch syndrome through germline genetic testing after positive universal tumor molecular screening. Among 5917 patients who underwent tumor IHC, 28% had abnormal staining. Among 3140 patients who underwent MSI analysis, 31% had MSI. Among patients with endometrial cancer, the weighted prevalence of Lynch syndrome germline mutations was 15% (95% confidence interval [CI], 11%‐18%) with deficient IHC staining and 19% (95% CI, 13%‐26%) with a positive MSI analysis. Among 1159 patients who exhibited a loss of MLH1 staining, 143 (13.7%) were found to be MLH1 methylation–negative among those who underwent methylation testing, and 32 demonstrated a germline MLH1 mutation (2.8% of all absent MLH1 staining cases and 22.4% of all MLH1 methylation–negative cases). Forty‐three percent of patients with endometrial cancer who were diagnosed with Lynch syndrome via tumor typing would have been missed by family history–based screening alone. Conclusions Despite the widespread implementation of universal tumor testing in endometrial cancer, data regarding testing results remain limited. This study provides predictive values that will help practitioners to evaluate abnormal results in the context of Lynch syndrome and aid them in patient counseling. This article presents a meta‐analysis evaluating mismatch repair immunohistochemistry, mutL homolog 1 (MLH1) methylation, and microsatellite instability analysis for screening patients with endometrial cancer for Lynch syndrome. To date, this is the largest study among patients with endometrial cancer to evaluate the outcomes of universal tumor testing for Lynch syndrome.